PENGARUH PENGGUNAAN COMIC STRIP TERHADAP KEMAMPUAN MENULIS TEKS TRANSAKSIONAL BAHASA JEPANG SISWA KELAS XII SMA PGRI 3 PADANG TAHUN AJARAN 2018/2019 - Prima Diana Khaled; Hendri Zalman; Meira Anggia Putri (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2018)
AbstractThis research is a quantitative experimental research. The purpose of this study is to find out about the effect of using comic strip to the 12th grader Student’s writing ability of Japanese transactional text at SMA PGRI 3 Padang. By using random sampling method, the population of this study is the 12th grader student at SMA PGRI 3 Padang school year 2018/2019.There are some indicators in order to achieve the objectives of this research, they are (1) find out how student's writing ability in Japanese transactional text without using comic strip media. (2) find out how student's writing ability in Japanese transactional text with using comic strip media. (3) find out that using comic strip has any effect to student’s writing ability in Japanese transactional text. The results of this research is the Japanese transactional text writing ability of experiment group is qualifying as ‘very good’ with an average 91,32. In other hand, the Japanese transactional text writing ability of control group is qualifying as ‘more than enough’ with an average 73,07. The Result of uji-t, can be concluded a hypothesis (H1) aceptablea in signification 5%  because Thitung > Ttabel (34,43> 2,02). In other words, usage comic strip has significant effect to the 12th grader Student’s writing ability of Japanese transactional text at SMA PGRI 3 Padang. So, it can be concluded that the Japanese transactional text writing ability of experiment group with comic strip media is ‘better’ than the control group without comic strip media. In other words, the usage of comic strip media is effective to student's writing ability in Japanese transactional text. Keywords: Transactional text, comic strip